Energy-Based Sound Source Localization with Low Power Consumption in Wireless Sensor Networks - Deng, Fang; Guan, Shengpan; Yue, Xianghu; Gu, Xiaodan; Chen, Jie; Lv, Jianyao; Li, Jiahong (IEEE transactions on industrial electronics (1982), 2017)
In this study, we show that the energy-based method of sound source localization can be successfully exploited for sound source localization under low power consumption conditions. Sound source localization is widely applied in battlefield environments where low power consumption is especially crucial and necessary for extending the lifespan of sensor nodes. We propose several variables that may (possibly) affect the path loss exponent. We provide data that shows that energy-based methods of sound source localization can accurately determine the appropriate path loss exponent and can improve localization accuracy. The results of our study also demonstrate that energy-based methods of sound source localization can significantly reduce localization errors by adjusting sensors' weight coefficients when ambient (background) noise exists. Our test results indicate that our method of source localization using low power consumption is consistently accurate and is able to determine sound source localization multiple times over an extended period.